SQSTM1/p62 variants in 486 patients with familial ALS from Germany and Sweden. - Yilmaz, Ruestem; Mueller, Kathrin; Brenner, David; Volk, Alexander E.; Borck, Guntram; Hermann, Andreas; Meitinger, Thomas; Strom, Tim M.; Danzer, Karin M.; Ludolph, Albert C.; Andersen, Peter M.; Weishaupt, Jochen H. (Neurobiology of Aging, 2020)
Several studies reported amyotrophic lateral sclerosis (ALS)-linked mutations in TBK1, OPTN, VCP, UBQLN2, and SQSTM1 genes encoding proteins involved in autophagy. SQSTM1 was originally identified by a candidate gene approach because it encodes p62, a multifunctional protein involved in protein degradation both through proteasomal regulation and autophagy. Both p62 and optineurin (encoded by OPTN) are direct interaction partners and substrates of TBK1, and these 3 proteins form the core of a genetic and functional network that may connect autophagy with ALS. Considering the molecular and conceptual relevance of the TBK1/OPTN/SQSTM1 "triangle," we here performed a targeted screen for SQSTM1 variants in 486 patients with familial ALS from Germany and Sweden by analyzing whole-exome sequencing data. We report 9 novel and 5 previously reported rare variants in SQSTM1 and discuss the current evidence for SQSTM1 as a primary disease gene for ALS. We conclude that the evidence for causality remains vague for SQSTM1 and is weaker than for the other autophagy genes, for example, TBK1 and OPTN.
EVALuna2:208319